2019
DOI: 10.1121/1.5084045
|View full text |Cite
|
Sign up to set email alerts
|

Born approximation of acoustic radiation force and torque on soft objects of arbitrary shape

Abstract: When the density and compressibility of an object are similar to the corresponding properties of the surrounding fluid and the incident sound field is a standing wave, the Born approximation may be used to calculate the acoustic radiation force and torque on an object of arbitrary shape. The approximation consists of integration over the monopole and dipole contributions to the force acting at each point within the region occupied by the object. The method is applied to axisymmetric objects, for which the forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The Born approximation for acoustic radiation force and torque exerted on nonspherical objects was obtained originally from the solution for the radiation force acting on a sphere of arbitrary size in terms of coefficients in the spherical wave expansions of the incident and scattered fields. 1 It was also shown that the Born approximation can be obtained by starting with Gor'kov's result for the radiation force on a small spherical particle in terms of the gradients of the potential and kinetic energy densities. 3 The analysis presented here follows the latter approach.…”
Section: Born Approximationmentioning
confidence: 99%
See 3 more Smart Citations
“…The Born approximation for acoustic radiation force and torque exerted on nonspherical objects was obtained originally from the solution for the radiation force acting on a sphere of arbitrary size in terms of coefficients in the spherical wave expansions of the incident and scattered fields. 1 It was also shown that the Born approximation can be obtained by starting with Gor'kov's result for the radiation force on a small spherical particle in terms of the gradients of the potential and kinetic energy densities. 3 The analysis presented here follows the latter approach.…”
Section: Born Approximationmentioning
confidence: 99%
“…These approximations of the force and torque are found to be accurate for homogeneous objects with dimensions on the order of the wavelength provided the compressibility and density of the object do not differ substantially from the corresponding values for the surrounding fluid. 1 Gor'kov's parameters f 1 and f 2 in Eqs. (2)-(4) are expressed as functions of position to allow for spatial variations of the compressibility and density within the object.…”
Section: Born Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Born approximation with numerical quadrature was used to obtain the radiation torque on a compressible spheroidal particle, with density and compressibility close to those of the surrounding fluid. [15] To date, the only analytical result to this problem was presented by Fan et al [16]. However, this investigation is mainly * gtomaz@fis.ufal.br focused on developing a general theoretical framework for arbitrarily shaped particles in the long-wavelength limit.…”
Section: Introductionmentioning
confidence: 99%